KENDALA DAN UPAYA MEWUJUDKAN SUPREMASI HUKUM - Indrati Rini (Perspektif, 2007)
The most material Iaiv resources comes from the living aspiration in the society. The Imv supremacy is enforced by the law enforcers who have experienced the handicaps in the society Public hearing is a tool of the law communication between government and society.